A critical review on the worldwide economist intelligence unit, Mercer and Monocle quality of life indicators - Ahmad Sarkawi, Azila; Abdullah, Alias; Md. Dali, Norimah (Academic Star Publishing, 2017)
Abstract: This article discusses selected worldwide indicators on quality of life vis-à-vis liveability. It comprises indicators promulgated by the Economist Intelligence Unit (EIU), Mercer (The global human resources consulting firm) and Monocle (The culture and lifestyle magazine). By index, the EIU refers it as Global Liveability Index; Mercer calls it Quality of Living Index while Monocle means it as Most Liveable City Index. The first index consists of 30 indicators grouped under 5 categories; the second constitutes 39 indicators broken down into 10 groups and the third is made up of 11 indicators with an addition of 22 metrics for its 2016 assessment. The study employed meta-ethnography qualitative approach by in-depth analysis and synthesis on the respective set of indicators. It is a systematic approach that enables comparison, analysis and interpretations to be made that can facilitate theorizing and practice. The analysis revealed the commonalities and differences amongst the three set of quality of life indicators. The result suggests that they are common in the sense that all of them are revolving around the five domains throughout their indicators, i.e., politics, economics, social, environment and infrastructure. However, they seem to be different in terms of the weightage given to each category of indicators and their detailing as the analysis on the top ten cities under respective organization revealed. Nonetheless, these commonalities and differences are contingent upon the respective organizational aim and objectives, methodology and emphasis. In short, one outstanding finding is that there is no “one-size-fit-all” kind of indicators as far as quality of life is concerned. It means different things to different people. Indeed, other factors that come into play include the culture and social system, the political and economic dimensions, and the environment. Key words: quality of life; liveability; sustainability; index JEL codes: F